Association between nurses’ perceptions of head nurse leadership style and their performance in nursing care delivery: A cross-sectional study - Maria Regina; Jamal Jamal; Frisa Anesia Amalah; Ayu Andira; Dedek Puspasari; Indra Frana Jaya KK (School of Health Sciences Al-Ma'arif, 2026)
Background: Nurses’ performance in delivering nursing care is a key indicator of hospital service quality. Ward head leadership may shape nurses’ work behavior through direction, motivation, supervision, and feedback. However, evidence regarding how nurses’ perceptions of head nurse leadership relate to nursing care performance in specific inpatient units remains limited. Objective: This study aimed to examine the association between nurses’ perceptions of head nurse leadership style and their performance in nursing care delivery in an inpatient ward. Methods: A quantitative correlational study with a cross-sectional design was conducted in the eighth-floor inpatient ward of RSUD Siti Fatimah in 2026. A total of 17 staff nurses were recruited using total sampling. Nurses’ perceptions of head nurse leadership style were measured using a leadership style questionnaire adapted from Nursalam, while nursing care performance was assessed using a 20-item nursing performance questionnaire adapted from Bakri. Data were analyzed using descriptive statistics and Spearman’s rank correlation with a significance level of α = 0.05. Results: Most respondents perceived the head nurse’s leadership style as good (n = 12; 70.6%), and most demonstrated good performance in nursing care delivery (n = 13; 76.5%). Among nurses with good leadership perceptions, 91.7% reported good nursing care performance. Spearman’s rank correlation showed a statistically significant positive association between nurses’ perceptions of head nurse leadership style and nursing care performance (r = 0.587; p = 0.013), indicating a moderate correlation. Conclusion: Nurses who perceived the head nurse’s leadership style more positively tended to report better performance in delivering nursing care. These findings suggest that effective ward-level leadership may support nursing care quality through clear direction, supervision, motivation, and constructive feedback. Strengthening leadership practices among head nurses is therefore important to enhance staff nurses’ performance and maintain the quality of inpatient nursing care.